PRACTICAL ANALYSES OF GENERATIVE AND VEGETATIVE PROPAGATION OF ORIGANUM MAJORANA L. - N.K.Askarova,; E.T. Akhmedov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article presents a practical analysis of the methods of generative and vegetative propagation of Origanum mаjorana L. (sweet marjoram). The research was conducted at the educational and experimental field of Tashkent State Agrarian University. To determine the germination rate of seeds under laboratory conditions, 100 seeds were placed in Petri dishes in four replications. The experiments revealed that seed germination under lаboratory conditions was relatively high, averaging between 80–85% across variants, with an overall average of 90%. Additionally, it was determined that when the temperature in laboratory conditions exceeded 23°C, the germination rate reached 90–95%.